2012
DOI: 10.1371/journal.pntd.0001886
|View full text |Cite
|
Sign up to set email alerts
|

Toxocara Seropositivity, Atopy and Wheezing in Children Living in Poor Neighbourhoods in Urban Latin American

Abstract: Background Toxocara canis and T. cati are parasites of dogs and cats, respectively, that infect humans and cause human toxocariasis. Infection may cause asthma-like symptoms but is often asymptomatic and is associated with a marked eosinophilia. Previous epidemiological studies indicate that T. canis infection may be associated with the development of atopy and asthma.ObjectivesTo investigate possible associations between Toxocara spp. seropositivity and atopy and childhood wheezing in a population of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 47 publications
5
61
2
3
Order By: Relevance
“…In different regions of Brazil, numerous cases of visceral and cutaneous larva migrans have been described for humans (MUSSO et al, 2007;SCHUSTER et al, 2013), and serological data have confirmed elevated level of exposure of humans to Toxocara spp. (FRAGOSO et al, 2011;SOUZA et al, 2011;MATTIA et al, 2012;MENDONÇA et al, 2012;SCHOENARDIE et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In different regions of Brazil, numerous cases of visceral and cutaneous larva migrans have been described for humans (MUSSO et al, 2007;SCHUSTER et al, 2013), and serological data have confirmed elevated level of exposure of humans to Toxocara spp. (FRAGOSO et al, 2011;SOUZA et al, 2011;MATTIA et al, 2012;MENDONÇA et al, 2012;SCHOENARDIE et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…10,27,[30][31][32]36,40 In all of these studies, a higher proportion of patients with asthma was found among those infected with Toxocara, which lends this infection greater relevance in terms of public health.…”
Section: Resultsmentioning
confidence: 94%
“…The study investigated the possible association between seropositivity for Toxocara, atopy, and childhood wheezing in a population of children in poor areas of the city. 40 Also in the city of Salvador, another study, which examined 338 middle-and lower-class individuals, found a higher prevalence of toxocariasis among those of the lower class and those with greater contact with dogs and cats. The study also showed that being in the lower class was associated with a higher risk of infection with T. canis.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have indicated the existence of an association between toxocariasis and other helminth infections, such as T. trichiura, Schistosoma mansoni, and A. lumbricoides 61,62 ; this association can be explained because the mechanism of transmission of Toxocara spp. is similar to other helminthes, and therefore, the risk of infection is similar in areas where these parasites co-exist.…”
Section: Discussionmentioning
confidence: 98%